2015
DOI: 10.1007/s13277-014-2187-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of steroidogenic factor-1 expression in ovarian cancer versus ovarian sex cord stromal tumor

Abstract: The significance of steroidogenic factor-1 (SF-1) in human ovarian tumor has not been fully investigated. The purposes of this study are to provide a meta-analysis for SF-1 and to determine whether SF-1 is associated with ovarian tumor progression and clinicopathological characteristics. A detailed literature search was made for related research publications written in English. Methodological quality of the studies was also evaluated. The data were extracted and assessed by two reviewers independently. Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…It encodes a human steroidogenic factor 1-protein (hSF1) that is involved in gonad development in both males and females [29]. hSF1 expression has been found to be significantly lower in ovarian cancer than in normal ovarian tissue [30] and mutations in NR5A1 are associated with primary ovarian insufficiency [31]. The third upstream regulator identified in our analysis was FOXA2, that has demonstrated favorable prognosis based on TCGA data [32] and was predicted to regulate six genes that were downregulated in omental samples vs primary tumor ( DLK1, GATA4, MAFA, MYOCD, NR1H4 and WNT5).…”
Section: Discussionmentioning
confidence: 99%
“…It encodes a human steroidogenic factor 1-protein (hSF1) that is involved in gonad development in both males and females [29]. hSF1 expression has been found to be significantly lower in ovarian cancer than in normal ovarian tissue [30] and mutations in NR5A1 are associated with primary ovarian insufficiency [31]. The third upstream regulator identified in our analysis was FOXA2, that has demonstrated favorable prognosis based on TCGA data [32] and was predicted to regulate six genes that were downregulated in omental samples vs primary tumor ( DLK1, GATA4, MAFA, MYOCD, NR1H4 and WNT5).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, clinical studies have suggested that ovarian tumors with functioning stroma secrete estradiol via the regulation of aromatase (CYP19), due to overexpression of SF-1 (103). A recent extensive meta-analysis of a wide range of ovarian cancer clinical studies was aimed at determining whether SF-1 is associated with ovarian tumor progression (115).…”
Section: Cancermentioning
confidence: 99%
“…19,20 While the aforementioned stains are helpful, this comes with a caveat since they can also be positive in sex cord-stromal tumors. 21,22 Hence, a known prior history sex cord-stromal tumor is crucial in the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Calretinin, which is a calcium‐binding protein, was first discovered in neural tissue and later found in adrenocortical cells, sex cord‐stromal cells, or mesothelial cells 19,20 . While the aforementioned stains are helpful, this comes with a caveat since they can also be positive in sex cord‐stromal tumors 21,22 . Hence, a known prior history sex cord‐stromal tumor is crucial in the diagnosis.…”
Section: Discussionmentioning
confidence: 99%